EFEK PERISTIWA POLITIK TERHADAP ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY PADASAHAM LQ-45 - Peti Mei Andari; Nedi Hendri; Jawoto Nusantoro Nusantoro (Jurnal Akuntansi AKTIVA, 2020)
ABSTRACT This study aims to verify whether the percentage of stock offerings, company age, and market timing affect the underpricing of companies that make Initial Public Offering (IPO)during 2014-2017. This research is a type of quantitative research and the data analysismethod used is multiple linear regression analysis. The sampling technique used in this studywas a purposive sampling technique with certain criteria, so that 76 sample companies wereobtained. Based on the results of data analysis that has been done, it is found that the percentage variable share offering has a significant effect on the level of underpricing, while the agevariable of the company has no significant effect on the level of underpricing. In addition, itwas found that the market timing variable had a significant effect on the level of underpricingand simultaneously the percentage of shares offering, company age, and market timing had asignificant effect on the level of underpricing of companies that conducted Initial PublicOffering (IPO) on the Indonesia Stock Exchange.